Approche communicative ou perspective actionnelle – état des lieux de l’enseignement/apprentissage des langues vivantes en Pologne - Sowa, Magdalena (Neofilolog, 2012)
The presented article reviews changes in the Polish system of foreign language teaching that have or should have occurred in the last half a century. The suggested time span encompasses the utilization of two major didactic methods which have been in use since the 1970s, i.e. the Communicative Method and the Task-Based Approach. The article consists of two major parts. The first one outlines the history and main methodological facets of the Communicative and Task-Based Approaches. The second part provides an analysis of the current state of affairs in Polish schools, based on surveys carried out among Polish teachers and students of foreign languages.